Classes of convex functions - Thomas Rosy; B. Adolf Stephen; K. G. Subramanian; Herb Silverman (International Journal of Mathematics and Mathematical Sciences)
We investigate a family that connects various subclasses of functions convex in the unit disk. We also look at generalized sequences for this family.